2018
DOI: 10.1002/ecs2.2365
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Nd isotope ratio as a tracer of marine animals: regional variation in coastal seas and causal factors

Abstract: 2018. Utility of Nd isotope ratio as a tracer of marine animals: regional variation in coastal seas and causal factors. Ecosphere 9(8):Abstract. Isotopic compositions of animal tissue are an intrinsic marker commonly used to trace animal origins and migrations; however, few isotopes are effective for this purpose in marine environments, especially on a local scale. The isotope ratio of the lanthanoid element neodymium (Nd) is a promising tracer for coastal animal migrations. Neodymium derives from the same geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…By contrast, neodymium isotopes ( 143 Nd/ 144 Nd ratios expressed as Ɛ Nd values) are indicated to be governed by continental geology, resulting in distinct geographic ocean profiles with high spatial resolution (Jeandel et al, 2007). Recent research demonstrated that Ɛ Nd values in the soft and hard tissues of bivalve molluscs are highly effective at identifying the origins of individuals at even small spatial scales (10s km) (Saitoh et al, 2018; Tanaka et al, 2022; Zhao et al, 2019). Concentrations of barium ratioed to calcium (Ba/Ca) are an additional candidate for universal provenance, as signatures reflect seawater composition (Bath et al, 2000; Walther & Thorrold, 2006), and are little affected by individual life history factors, such as physiology or diet (Grammer et al, 2017; Hüssy et al, 2021; Martino et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, neodymium isotopes ( 143 Nd/ 144 Nd ratios expressed as Ɛ Nd values) are indicated to be governed by continental geology, resulting in distinct geographic ocean profiles with high spatial resolution (Jeandel et al, 2007). Recent research demonstrated that Ɛ Nd values in the soft and hard tissues of bivalve molluscs are highly effective at identifying the origins of individuals at even small spatial scales (10s km) (Saitoh et al, 2018; Tanaka et al, 2022; Zhao et al, 2019). Concentrations of barium ratioed to calcium (Ba/Ca) are an additional candidate for universal provenance, as signatures reflect seawater composition (Bath et al, 2000; Walther & Thorrold, 2006), and are little affected by individual life history factors, such as physiology or diet (Grammer et al, 2017; Hüssy et al, 2021; Martino et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of the isotope tracking method is that it can reveal migration routes of individual animals over a prolonged timescale (the timescale of bone growth). Although the spatial resolution of the method depends on the spatial scale of isotopic gradients among habitats, the use of additional isoscapes based on radiocarbon content (Larsen et al 2018) or neodymium stable isotope ratios (Saitoh et al 2018) could help enable finer‐scale determinations of fish migration routes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focus on neodymium (Nd), which is becoming widely applied to many areas outside of traditional geochemistry and geochronology. Recent applications include paleoceanography, nuclear forensics, and source attribution with each new application necessitating the analysis of smaller sample sizes. For example, isotope ratios of neodymium ( 143 Nd/ 144 Nd) extracted from marine animal samples have been used as intrinsic markers of local geology to track their origin …”
Section: Introductionmentioning
confidence: 99%
“…1−3 For example, isotope ratios of neodymium ( 143 Nd/ 144 Nd) extracted from marine animal samples have been used as intrinsic markers of local geology to track their origin. 4 While multicollector inductively coupled plasma mass spectrometry has become popular for such sensitive measurements, the overall efficiency (number of atoms analyzed relative to the number of atoms available) of these systems is 1−2%. 5,6 By contrast, the efficiency of thermal ionization mass spectrometry (TIMS) measurements varies with the analyte of interest, quality of sample preparation, and loading technique.…”
Section: ■ Introductionmentioning
confidence: 99%